Cancer vaccines: a newer front of immunotherapy - Puri, Sonia; Goel, Naveen Krishan; Chadha, Veenal; Bhandari, Praizy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Vaccines have been used as a promising instrument over the years to combat the dreadful communicable diseases. But now owing to epidemiological transition as the burden of non-communicable diseases has increased, efforts are now being made globally to use this weapon for non-communicable diseases like cancer. Cancer vaccines belong to a class of substances known as “biological response modifiers”. These work by stimulating or restoring the immune system’s ability to fight infections and disease. There are two broad types of cancer vaccines: Preventive (or prophylactic) vaccines and Treatment or therapeutic vaccines. Cancer treatment vaccines are made up of cancer cells, parts of cells or pure antigens. Sometimes a patient’s own immune cells are removed and exposed to these substances in the lab to create the vaccine. Cancer treatment vaccines differ from the vaccines that work against viruses. These vaccines try to get the immune system to mount an attack against cancer cells in the body. Instead of preventing disease, they are meant to get the immune system to attack a disease that already exists. Preventive vaccines are intended to prevent cancer from developing in healthy people. And in fact, many evidence-based studies have proven the decrease in morbidity and mortality in various cancers by usage of some of the vaccines like cervical cancer vaccine etc. The biggest challenges currently facing preventive anti-cancer vaccines are clinical, social, and economic in nature. This article is an effort to highlight the advances in various cancer vaccines, so done, to use them on preventive and therapeutic front.